(untitled) (Agroindustria, Sociedad y Ambiente, 2016)
This article is based on research framed in the qualitative paradigm, the type meets the hermeneutics-dialectics, and aims to "generate a theoretical corpus on the edu-communication as a new perspective of the educational role of communication in the university context. " The collection and interpretation of literature theoretical material was used for the realization of the corpus besides participant observation; a structured interview based on the hermeneutic circle of dialogue between four (4) classics of communication and education, such as Simon Rodriguez, Jurgen Habermas, Paulo Freire and Edgar Morin, thus he also obtained interesting responses was applied, matches in speeches that led to develop categories and sub-categories thus emerged that allowed shed conclusive reflections and contributions among which; first understand that education is a necessity, teachers in charge to take the reins of the process must have appropriate professional profile that depart from their experiences and will be in continuous development and comprehensive academic preparation, just as you can not forget if there is a strong relationship between education and communication and not be conceived without the other, the media will come to those tools that facilitate the teaching-learning process, all to achieve change tomorrow’s education in universities and edu-communication make true.